Make a Difference - Nick Vujicic (PMA Music Foundation, 2015)
Through eight chapters, Make a Difference describes the philosophy of life Nick has learnt and the bullying he has encountered while he was growing up. The stories are also about how Nick adjusted his emotion and attitude, how he didn't let external obstacles and limitations affect his faith and determination, and how he transformed himself one step at a time. Not only did he change himself, Nick travels around the world to encourage numerous peope who have also been hurt and discriminated against through giving talks and sharing his own experiences. Like Nick, all of us should believe in ourselves and make a difference in life!